2022
DOI: 10.1007/s11606-021-07199-1
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Survival After In-Hospital Cardiopulmonary Resuscitation

Abstract: Background: Older adults face high mortality following resuscitation efforts for in-hospital cardiac arrest.Less is known about the role of frailty in survival to discharge after in-hospital cardiopulmonary resuscitation.Objective: To investigate whether frailty, measured by the Clinical Frailty Scale, is associated with mortality after cardiopulmonary resuscitation following in-hospital cardiac arrest in older adults in the USA.Design: Retrospective cohort study.Participants: Patients ≥ 65 years who had under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…We modified the frailty cut-off score in one study to include a CFS score of four in the non-frail group, consistent with other studies and standard clinical practices. 22 Percentage mortality in non-frail participants undergoing CPR was 71.6% compared to 90.2% in frail participants. One study found that no frail patients survived to discharge, 19 while another found only one frail patient survived.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…We modified the frailty cut-off score in one study to include a CFS score of four in the non-frail group, consistent with other studies and standard clinical practices. 22 Percentage mortality in non-frail participants undergoing CPR was 71.6% compared to 90.2% in frail participants. One study found that no frail patients survived to discharge, 19 while another found only one frail patient survived.…”
Section: Resultsmentioning
confidence: 94%
“…Eight studies comparing the outcomes in frail versus non-frail individuals receiving CPR for cardiac arrest were included in a narrative synthesis ( Table 1 ). 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 Of these, seven studies presented sufficient data for inclusion in quantitative synthesis. All studies included in meta-analysis were of a retrospective observational design and considered to be of high methodological quality ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations